Association of per- and polyfluoroalkyl substances with gout risk: a cross-sectional analysis of NHANES 2007–2018 data emphasizing mixture effects - Haixin Feng; Siran Li; Shiqing Huang; Linxi He; Ruihao Huang; Renhuizi Wei; Xin Peng; Haiyi Yan; Chongxiang Xiong; Bingsong Zhang (Frontiers in Public Health)
ObjectiveThis study examined associations between serum concentrations of per- and polyfluoroalkyl substances (PFASs) and gout risk in the U.S. adult population using the National Health and Nutrition Examination Survey (NHANES) 2007–2018 data. And assessing the potential intermediary effect of uric acid.MethodsThe study included 8,494 participants, with 385 having gout. Four PFAS compounds (PFOA, PFOS, PFHxS, PFNA) were measured. PFOS is the most prevalent PFAS in the environment, biota, and human tissues. It is rapidly absorbed and accumulates in the liver, kidneys, and blood, binding to serum albumin and low-density lipoprotein. PFOA is highly persistent in the body, mainly accumulating in the kidneys and liver through enterohepatic circulation, posing risks due to its difficulty in metabolism and excretion. PFHxS has the longest metabolic half-life in humans (7.3 years) and bioaccumulates in the endocrine, immune, nervous, and reproductive systems. PFNA is the second most detected PFAS in human serum after PFOS. It is more likely to accumulate and express toxicity in the reproductive organs, liver, and immune system compared to PFOS and PFOA. Multivariate logistic regression and weighted quantile sum regression were used to assess individual and mixture effects. Mediation analysis was conducted to estimate effect of uric acid.ResultsIn fully adjusted model, the associations were nonsignificant, with PFOA showing a marginally positive association. Mixture analysis revealed a significant positive association with gout risk across all models. PFOS was the largest contributor to the mixture effect. Stronger associations were observed in old people and females. Sensitivity analyses confirmed the robustness of these findings. Mediation analysis indicated significant intermediary effect of uric acid in the associations of PFAS with risk of gout, with the mediated proportion ranging from 48 to 77%.ConclusionThis study provides evidence for a potential link between PFAS exposure and gout risk, particularly when considering mixtures. While associations with individual PFASs are largely explained by demographic and lifestyle factors, the persistent association of mixtures with gout risk highlights the importance of considering combined exposures in environmental health research. Uric acid level plays a crucial intermediary effect.